2022
DOI: 10.1371/journal.pone.0263899
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring biological water quality by volunteers complements professional assessments

Abstract: Progressively more community initiatives have been undertaken over last decades to monitor water quality. Biological data collected by volunteers has been used for biodiversity and water quality studies. Despite the many citizen science projects collecting and using macroinvertebrates, the number of scientific peer-reviewed publications that use this data, remains limited. In 2018, a citizen science project on biological water quality assessment was launched in the Netherlands. In this project, volunteers coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 74 publications
0
14
0
Order By: Relevance
“…Many of the long-standing citizen science programmes have involved the collection of biological data, but these are often confined to a few countries and focussed on macroinvertebrate water quality indicators. For example, in the USA there are approximately 1700 volunteer water quality monitoring programmes ( http://volunteermonitoring.org/ ) and according to Peeters et al ( 2022 ), circa 50% of these involve macroinvertebrate indicators. Other well-established programmes noted by Peeters et al ( 2022 ) include the British Anglers’ Riverfly Monitoring Initiative (described in more detail later) and the New-Zealand Wai Care programme ( https://localgovernmentmag.co.nz/wai-care-programme/ ).…”
Section: Methods Appropriate For Citizen Science Monitoring In Swbs I...mentioning
confidence: 99%
See 2 more Smart Citations
“…Many of the long-standing citizen science programmes have involved the collection of biological data, but these are often confined to a few countries and focussed on macroinvertebrate water quality indicators. For example, in the USA there are approximately 1700 volunteer water quality monitoring programmes ( http://volunteermonitoring.org/ ) and according to Peeters et al ( 2022 ), circa 50% of these involve macroinvertebrate indicators. Other well-established programmes noted by Peeters et al ( 2022 ) include the British Anglers’ Riverfly Monitoring Initiative (described in more detail later) and the New-Zealand Wai Care programme ( https://localgovernmentmag.co.nz/wai-care-programme/ ).…”
Section: Methods Appropriate For Citizen Science Monitoring In Swbs I...mentioning
confidence: 99%
“…For example, in the USA there are approximately 1700 volunteer water quality monitoring programmes ( http://volunteermonitoring.org/ ) and according to Peeters et al ( 2022 ), circa 50% of these involve macroinvertebrate indicators. Other well-established programmes noted by Peeters et al ( 2022 ) include the British Anglers’ Riverfly Monitoring Initiative (described in more detail later) and the New-Zealand Wai Care programme ( https://localgovernmentmag.co.nz/wai-care-programme/ ). Whilst monitoring water quality can be based at relatively high-level taxonomic identification (e.g.…”
Section: Methods Appropriate For Citizen Science Monitoring In Swbs I...mentioning
confidence: 99%
See 1 more Smart Citation
“…nl'. The web application then calculates a water quality score (Peeters et al 2022) based on the information provided and sends this score back to the volunteer as a reward. A comparison has been made between data collected in the Netherlands by professionals and volunteers and this showed that only a minority of the samplings by professionals was in the urban environment (roughly 10% of yearly investigations) while volunteers sampled more frequently (roughly 20% of their samples) (Peeters et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The web application then calculates a water quality score (Peeters et al 2022) based on the information provided and sends this score back to the volunteer as a reward. A comparison has been made between data collected in the Netherlands by professionals and volunteers and this showed that only a minority of the samplings by professionals was in the urban environment (roughly 10% of yearly investigations) while volunteers sampled more frequently (roughly 20% of their samples) (Peeters et al 2022). Since only a limited number of private garden ponds has been monitored in the past in the Netherlands (Peeters et al 2022), knowledge on the biodiversity and water quality of these aquatic systems in the urban environment remains very limited.…”
Section: Introductionmentioning
confidence: 99%